2022
DOI: 10.35848/1347-4065/ac43e4
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-compact leaky integrate-and-fire neuron with long and tunable time constant utilizing pseudo resistors for spiking neural networks

Abstract: Spiking neural networks (SNNs) inspired by biological neurons enable a more realistic mimicry of the human brain. To realize SNNs similar to large-scale biological networks, neuron circuits with high area efficiency are essential. In this paper, we propose a compact leaky integrate-and-fire (LIF) neuron circuit with a long and tunable time constant, which consists of a capacitor and two pseudo resistors (PRs). The prototype chip was fabricated with TSMC 65 nm CMOS technology, and it occupies a die area of 1392… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[25] As for the action mechanism of biological neurons depicted in Figure 3a, if the neurons receive sufficient input spikes from the adjacent neurons through joint synapses, its membrane potential may exceed a certain membrane potential threshold, leading to the transmition of the spike stimuli into the axon, which is often referred to as output firing. [6] Simply put, one fundamental function of biological neurons, that is, the complete realization of information exchange, can be achieved by receiving, integrating, transmitting, and outputting information. [26] It has been widely reported that the CFs-based TS devices can be used in realizing various neuronal characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] As for the action mechanism of biological neurons depicted in Figure 3a, if the neurons receive sufficient input spikes from the adjacent neurons through joint synapses, its membrane potential may exceed a certain membrane potential threshold, leading to the transmition of the spike stimuli into the axon, which is often referred to as output firing. [6] Simply put, one fundamental function of biological neurons, that is, the complete realization of information exchange, can be achieved by receiving, integrating, transmitting, and outputting information. [26] It has been widely reported that the CFs-based TS devices can be used in realizing various neuronal characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Structurally speaking, a hardware friendly and energy efficient SNN is composed of two fundamental information processing elements, that is, artificial neurons and synapses, which need to meet the requirements of high-density integration and excellent stability. [6,7] In order to guarantee the synapse matrix works effectively, volatile threshold switching (TS) devices are needed to simulate integrate-and-fire function of neurons. [8] Nevertheless, many neural devices used for SNNs are the mainstream complementary metal-oxidesemiconductor (CMOS) neurons that are indispensable for realizing of sophisticated circuits, which are considered unsuitable for large-scale network implementation due to their large area and low efficiency.…”
Section: Introductionmentioning
confidence: 99%